The Horns of Moses - Jefferson, Lee M. (Biblical archaeology review, 2023)
he article explores the origins and symbolism of Michelangelo's sculpture of Moses and why he is depicted with horns. It delves into the historical and theological context of the Bible, the role of Jerome's translation, and how the portrayal of Moses with horns shifted from a mark of respect to a derogatory symbol in Christian art due to anti-Jewish sentiment in medieval Europe.